Fundamentals of Teaching Through Art-Pedagogy - Mamadaliyev Kamolidin Raxmatulloyevich (Euro Asian Journal Publishing, 2025)
This article reveals the content and essence of art- pedagogy. Particular attention is paid to teaching methods using art- pedagogy. Learning using art pedagogy is based on serving the professional development of students.
Keywords: culture; art pedagogy; art therapy